Nematode resistance and resistance mechanism in sweet potato cultivars 'bophelo', 'bosbok' and mvuvhelo' to meloidogyne incognita - Makhwedzhana, Mmboniseni Meshack (My University, 2018)
Meloidogyne incognita race 2 is internationally recognised as one of the most aggressive Meloidogyne species and it is also widely distributed in Limpopo Province, where it occurs alone or as mixed populations with other Meloidogyne species. Traditionally, Meloidogyne species had been managed using synthetic chemical nematicides, most of these products had been withdrawn from agro-chemical markets due to their environment-unfriendliness. Following the withdrawal of synthetic chemical nematicides, nematode resistance had been the most preferred strategy for managing high nematode population densities. The availability of nematode resistant genotypes in sweet potato (Ipomoea batatas) would enhance the use of resistance in managing Meloidogyne species and races in Limpopo Province. Generally, should post-infectional nematode resistance be available in the test sweet potato cultivars, the information would be relayed to plant breeders for use as source of introgression in various commercial cultivars where nematode-resistant genotypes do not exist. The objectives of the study, were to determine: (1) Host-status and host-sensitivity in sweet potato cv. ʹBopheloʹ, ʹBosbokʹ and ʹMvuvheloʹ to M. incognita race 2. (2) the existing nematode resistance mechanism in any of the test cultivars that had resistance to M. incognita race 2. For achieving Objective 1, eight treatments namely, 0, 25, 50, 125, 250, 625, 1250 and 3125 eggs and second stage-juveniles (J2) M. incognita race 2 were used under greenhouse trials for each cultivar. To achieve Objective 2, sweet potato plants were inoculated with 100 J2 with four plants harvested every other day for 30 days counting to 15 harvesting times. At 56 days after inoculation, cv. ʹBopheloʹ had reproductive factor (RF) values above unity for M. incognita race 2 and plant growth variables were reduced. Therefore, the cultivar was a susceptible host to M. incognita race 2 and mechanism trial was not conducted for this cultivar. Meloidogyne incognita race 2 failed to reproduce on cultivars ʹBosbokʹ and ʹMvuvheloʹ whereas nematode infection did not affect plant growth and therefore, the two cultivars were resistant to M. incognita race 2. Mechanisms of resistance to M. incognita race 2 on cultivars ʹBosbokʹ and ʹMvuvheloʹ demonstrated significance existence of (1) necrotic spots, (2) poorly developed giant cells, (3) formation of rootlet interferences (4) absence of root galls and (5) non-detectable J2 in roots. All these features suggested the existence of post-infectional nematode resistance in the two cultivars to M. incognita race 2. In conclusion, cultivar ʹBopheloʹ was susceptible to M. incognita race 2, whereas cultivars ʹBosbokʹ and ʹMvuvheloʹ were resistant to M. incognita race 2, with the evidence of post-infectional nematode resistance to the nematode species
Thesis (M.Agric. (Plant Production)) -- University of Limpopo, 2018
Keywords: Nematode resistance; Sweet potato; Meloidogyne incognita; Nematode diseases of plants; Root-knot nematodes